Chemical Pulps for Writing and Printing Papers from Albizia moluccana - Guha, S. R. D.; Karira, B. G. (Indian Forester, 1981)
Laboratory experiments on production of chemical pulps from Albizia maluccana for writing and printing papers by sulphate process are described. The average fibre length of the pulp was 0.98 mm and the average fibre diameter was 0.18 mm. Easy bleaching pulps in good yields with satisfactory strength properties could be prepared under suitable conditions of digestion. The investigation reported in this paper has shown that Albizia moluccana is a promising fibrous raw material for the manufacture of white writing and printing papers. For comparison results obtained from Albizia lebberk and Albizia procera are also included. This species is very similar to Albizia labbeck and Albizia procera investigated earlier in this laboratory.